1976
DOI: 10.1111/j.1365-2621.1976.tb00694.x
|View full text |Cite
|
Sign up to set email alerts
|

HEAT TREATMENT: A PROCESS TO CONTROL THE DEVELOPMENT OF THE HARD‐TO‐COOK PHENOMENON IN BLACK BEANS (Phaseolus vulgaris)

Abstract: Whole black beans were heat treated for 2, 5 and 10 mm at 121°C and 10, 20 and 30 mm under steam (98°C). Heat treatments did not affect the physical appearance of the grams but significantly (P < 0.05) decreased the development of the hard-tocook phenomenon in seeds stored at 25°C and 70% RH for 9 months. After 9 months of storage no significant difference (P < 0.05) was found between hardness of cooked beans subjected to the shortest heat treatments and control samples kept at 4°C. Nitrogen solubility in O.Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 6 publications
1
34
1
Order By: Relevance
“…It seems that although the lesser heat treatment caused initial softening, it eventually led to the development of increased hardness. A similar response to that of Aguilera & Steinsapir (1985) was reported by Molina et al ( 1976), although in this case the beans were either retorted or heated under steam, both processes allowing more heat penetration due to the higher temperature, time and/or water content.…”
Section: Cooked Hardnesssupporting
confidence: 71%
“…It seems that although the lesser heat treatment caused initial softening, it eventually led to the development of increased hardness. A similar response to that of Aguilera & Steinsapir (1985) was reported by Molina et al ( 1976), although in this case the beans were either retorted or heated under steam, both processes allowing more heat penetration due to the higher temperature, time and/or water content.…”
Section: Cooked Hardnesssupporting
confidence: 71%
“…After harvest, the dry seeds, with an average moisture content of 10.1%w/w, were stored in plastic bags for two months at 4~ before being used in the present study. Molina et al [14], found that storage at 4 ~ prevented development of the hard-to-cook effect of black beans even after 9 months.…”
Section: Introductionmentioning
confidence: 97%
“…In their findings, cell wall material from hard beans had a lamellate appearance, not observed in the control; thus, cellulose deposition, a precursor of lignification, was implicated. A study by Molina et al (99) reported an increase in lignified protein in bean cotyledons (P. vulgaris) during storage at ACs (25°C and 70% RH). This was corroborated by Hincks and Stanley (81) and Srisuma et al, (92) who reported substantial increases in Klason lignin and lignified protein contents that were correlated to an increase in cooking time.…”
Section: Lignification and Phenolic Compoundsmentioning
confidence: 99%